Effectiveness of Moringa Leaf Decoction as Supportive Therapy for Anemia Patients - Rezqiqah Aulia Rahmat; Reffi Dhamayanti (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Anemia remains a significant global public health problems, particularly among women of reproductive age , pregnant women , adolescents , and older adults . It is characterized by low hemoglobin levels , resulting in reduced oxygen-carrying capacity of the blood . Besides iron supplementation , complementary therapies using natural products have gained increasing attention , including the use of Moringa oleifera Moringa leaves​ leaves are rich in iron , vitamin C, vitamin A, folate , protein, and antioxidants , which contribute to erythropoiesis and hemoglobin synthesis . This study aimed to review scientific evidence regarding the effectiveness of Moringa leaf decoction as an adjunctive therapy for improving hemoglobin levels in patients with anemia. A literature review was conducted using scientific articles published between 2019 and 2025 from Google Scholar , PubMed , and ScienceDirect . Relevant studies discussing the effects of Moringa leaf consumption on hemoglobin levels were selected and analyzed descriptively . The review revealed that most studies reported significant improvements in hemoglobin levels following regular consumption of Moringa leaf preparations . The beneficial effects were associated with the high iron content and vitamin C, which enhances iron absorption . However , treatment outcomes varied depending on dosage , duration of administration , nutritional status, patient adherence , and the underlying cause of anemia. Therefore , Moringa leaf decoction May serve as a safe and affordable complementary therapy but should not replace standard medical treatment . Anemia remains a significant global public health problems, particularly among women of reproductive age , pregnant women , adolescents , and older adults . It is characterized by low hemoglobin levels , resulting in reduced oxygen-carrying capacity of the blood . Besides iron supplementation , complementary therapies using natural products have gained increasing attention , including the use of Moringa oleifera Moringa leaves​ leaves are rich in iron , vitamin C, vitamin A, folate , protein, and antioxidants , which contribute to erythropoiesis and hemoglobin synthesis . This study aimed to review scientific evidence regarding the effectiveness of Moringa leaf decoction as an adjunctive therapy for improving hemoglobin levels in patients with anemia. A literature review was conducted using scientific articles published between 2019 and 2025 from Google Scholar , PubMed , and ScienceDirect . Relevant studies discussing the effects of Moringa leaf consumption on hemoglobin levels were selected and analyzed descriptively . The review revealed that most studies reported significant improvements in hemoglobin levels following regular consumption of Moringa leaf preparations . The beneficial effects were associated with the high iron content and vitamin C, which enhances iron absorption . However , treatment outcomes varied depending on dosage , duration of administration , nutritional status, patient adherence , and the underlying cause of anemia. Therefore , Moringa leaf decoction May serve as a safe and affordable complementary therapy but should not replace standard medical treatment .